The Influence of Newspaper Ownership on the Objectivity of the Coverage of Nigeria’s 2015 Presidential Election - Mordi, Frederick; Ogbu, Silk Ugwu (European Scientific Journal, ESJ, 2017)
This paper examines the impact of politician-businessperson-owned (PBO) newspapers on the objectivity of the reportage of the 2015 presidential election in Nigeria, by some selected media organisations. Adopting analysis of documentary evidence as methodology, the study examines the dominant themes of some PBO newspapers during their coverage of the election. This was done with a view to establishing their level of objectivity, which is defined in terms of whether these media organisations gave equitable coverage to all the 26 political parties and their candidates; and their level of compliance with professional ethics. Using gatekeeping theory as main theoretical framework, the paper finds that media owners, and not the editors, appear to be the gatekeepers. The paper recommends proper regulation of media organisations in the country to ensure that they meet stipulated ethical standards.